Digital Cooperatives and MSMEs as Drivers of People's Business Modernization to Strengthen the People's Economy in Indonesia - Nurlaili, Eka; Subroto, Waspodo Tjipto; Sakti, Norida canda (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This study examines the role of digital cooperatives and MSMEs in driving business modernization to strengthen Indonesia's economy. Cooperatives and MSMEs are essential for economic growth and community welfare, significantly contributing to Indonesia's GDP and employment. However, they face challenges in modernization due to limited technology access and management issues. Using a systematic literature review, this research analyzes the influence of digital transformation on cooperatives and MSMEs, identifying digital technology adoption, collaborative approaches, and governmental support as key factors in modernization. Findings highlight that a structured digital framework, social capital, and policy backing enable cooperatives and MSMEs to enhance operational efficiency, resilience, and competitiveness. This modernization model offers insights into fostering a sustainable, inclusive economy through digitalized cooperative structures. The research underscores the need for ongoing digital adaptation, emphasizing cooperatives' dual role in community development and economic resilience.